Etika Perang dalam Perspektif Hadis - Abdullah Noerkholis; Muhammad Alif (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The Islamic ethics of war are an important part of Sharia teachings, emphasizing that moral and humanitarian principles must be upheld during times of conflict. Islam does not view war as an ultimate goal, but rather as a last resort for defending justice, fighting oppression, and protecting people from real threats. In this context, the Quran and the sayings of the Prophet Muhammad (PBUH) provide clear guidelines for Muslims to follow when engaging in war. These include prohibitions against killing non-combatants, such as women, children, and the elderly. They also prohibit dangerous public institutions, worship, and neighborhoods. Muslims are also obligated to treat prisoners of war humanely. The Qur'an and Hadith clearly regulate the treatment of prisoners of war, emphasizing the principles of justice, respect for humanity, and the rights of individuals in the midst of warfare. Understanding and applying Islamic war ethics invites Muslims to avoid an aggressive attitude and to use war as a means of defending noble values while maintaining human dignity. This research uses the thematic method to analyze hadiths about war. The results of this research are broadly covered in three areas: the definition of war, the prohibition of cruel actions in war, and war strategies. The results of the research are expected to provide insight as well as a foundation for further discussion.